Effects of internet-based cognitive behavioral therapy on anxiety and depressive symptoms among patients with cardiovascular and cerebrovascular diseases: a systematic review and meta-analysis - Wang, Shuangyu; Gao, Lishuo; Wang, Congyu; Bai, Jinbing; Shen, Mengshuang; Zhao, Xuejie; Lin, Mei (Frontiers in Psychiatry, 2025)
BackgroundThis study aimed to evaluate the effectiveness of Internet-based Cognitive Behavioral Therapy (ICBT) in reducing anxiety and depressive symptoms among patients with cardiovascular diseases (CVDs) and to explore how intervention characteristics, such as module number and program duration, influence treatment outcomes.MethodsA systematic review and meta-analysis were conducted by searching eight databases, including PubMed, Embase, and Cochrane Library, for randomized controlled trials (RCTs) published up to December 2023. Studies involving adult CVD patients with anxiety or depressive symptoms who underwent ICBT interventions were included. Statistical analyses used random-effects models, with subgroup analyses performed to assess the impact of intervention format, module number, and program duration. Sensitivity and publication bias assessments ensured the robustness of the findings.ResultsEight RCTs with 1177 participants were included. ICBT significantly reduced depressive symptoms (SMD = -0.32, 95% CI [-0.56, -0.08], p < 0.015) and anxiety symptoms (SMD = -0.37, 95% CI [-0.68, -0.06], p < 0.001). Subgroup analysis indicated that self-guided ICBT was more effective than therapist-guided ICBT. Programs with fewer than eight modules were more effective for anxiety, while those with eight or more modules were more effective for depression. Shorter programs (< 9 weeks) were better for anxiety, whereas longer programs (≥ 9 weeks) were more effective for depression.ConclusionsICBT is an effective intervention for managing anxiety and depression in CVD patients. Tailoring ICBT interventions based on symptom type, module number, and program duration can optimize outcomes. Future research should explore personalized, long-term strategies to enhance effectiveness and safety.